The impact of single exposure advertising and socioeconomic status on parenting behavior and children's food choice - Boyd, Aaron (Kansas State University, 2011)
Background: Childhood obesity represents a major public health problem. Increasing public and political attention has been directed towards the role of child-directed food advertising in the growth of childhood obesity. As a potential solution, scientists have begun to focus on children’s responses to advertising and on how parents can potentially modify or reduce advertising effects. This study explored the impact of food advertising on parent behavior and children's food choice and how these potential effects are moderated by household socioeconomic status (SES). Methods: Fifty-eight parent-child dyads (ages of 4-6) participated in a true experimental design where half the sample was randomized to be exposed to advertising and categorized as low income or higher income (qualified for free and reduced lunch, n = 11; paid, n = 18) and half was randomized into a control condition (qualified for free and reduced lunch, n = 12; paid, n = 17). Parents completed a questionnaire, viewed a cartoon with energy dense (ED) food commercials or control commercials with their children, and children subsequently choose either an energy dense food or a fruit or vegetable. Throughout the experiment parent and child behavior was videotaped. Binary logistic regression was conducted to examine the impact of advertising and household SES on parent behaviors and children’s food choice. Results: Advertisements had no effect on food choice. More low-income children chose a fruit or vegetable over an energy dense food (OR = 5.8), regardless of whether or not they were exposed to advertising (p<.05). Parents were more likely to be uninvolved in mediating children’s food choice when they were not exposed to advertising. Parents were also less likely to agree to energy dense foods after being exposed to energy dense food advertising compared to control advertising. However, SES moderated the advertising-parental practice effect for parental agreement to an ED food. After exposure to food advertising, more low-income parents agreed to an energy dense food compared to higher income parents. (p<.05). Conclusion: This study has demonstrated a link between advertising exposure and parenting behavior. Results suggest that this relationship may be moderated by socioeconomic status. This encouraging result may indicate that low-income parents are unaware of the various ways advertising could influence their children. Thus, future attempts should be made to investigate whether interventions that target parent-child communication strategies may empower parents to effectively curb unwanted advertising effects in children.
Keywords: Food advertising; Parenting; Health Sciences (0566)